A tetramic acid derivative with protein tyrosine phosphatase 1B inhibitory activity and a new nortriterpene glycoside from the Indonesian marine sponge Petrosia sp. Issue 4 (15th February 2017) - Maarisit, Wilmar; Yamazaki, Hiroyuki; Kanno, Syu-ichi; Tomizawa, Ayako; Rotinsulu, Henki; Wewengkang, Defny S.; Sumilat, Deiske A.; Ukai, Kazuyo; Kapojos, Magie M.; Namikoshi, Michio
Graphical abstract: Abstract: During the search for protein tyrosine phosphatase 1B (PTP1B) inhibitors from marine organisms, the known tetramic acid derivative, melophlin C (1 ), was isolated as an active component together with the new nortriterpenoid saponin, sarasinoside S (2 ), and three homologues: sarasinosides A1 (3 ), I1 (4 ), and J (5 ), from the Indonesian marine sponge Petrosia sp. The structure of2 was elucidated on the basis of its spectroscopic data. Compound1 inhibited PTP1B activity with an IC50 value of 14.6 μM, while compounds2 –5 were not active at 15.2–16.0 μM. This is the first study to report the inhibitory effects of a tetramic acid derivative on PTP1B activity.